Somatotype of competitive youth soccer players from Brazil - Fidelix, Y. L.; Berria, J.; Pinheiro Ferrari, E.; Goncalves Ortiz, J.; Cetolin, T.; Petroski, E. L. (Journal of Human Kinetics, 2014)
The aim of this study was to identify the morphological configuration of youth athletes from professional soccer clubs and to verify their differences according to the tactical position on the field. Overall, 67 male players aged 15 to 17 years were evaluated. The examined anthropometric measurements included body mass, body height, skinfolds (triceps, subscapular, supraspinal and medial calf), girths (flexed and tensed arm and calf) and breadths (humerus and femur). For statistical purposes, analysis of variance and post hoc Bonferroni and Kruskal-Wallis tests were used. We concluded that goalkeepers were heavier and taller than center backs (p = 0.015 and p = 0.001), midfielders (p = 0.005 and p <0.001) and center forward players (p = 0.024 and p <0.001). The average somatotype for defense, forward and goalkeeper positions was a balanced mesomorph. Midfield players showed ectomorphic-mesomorph characteristics. It was concluded that goalkeepers were characterized as being taller and heavier and that somatotype features of athletes were similar between positions, except for midfield players.